TAX AVOIDANCE AS A RESULT OF DEBT LEVELS AND DEFERRED TAX - Sudjiman, Lorina Siregar; Sudjiman, Paul Eduard (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Enter Listed on the Indonesia Stock Exchange and included in the SRI-KEHATI Index for the years 2021-2023, the purpose of this research is to assess the impact of debt levels and deferred taxes on tax avoidance. The Completed Item All of the descriptive methods that were utilized in this investigation were quantitative. The framework of this study makes use of secondary data that was obtained from several information sources, including www.idx.com. Throughout the three-year observation period (2021-2023), sixty data points that satisfy particular criteria were gathered from twenty-five companies that were selected through the use of a purposive sampling approach. To study the data, various statistical methods were utilized, including descriptive statistics with classical assumption testing, multiple linear regression analysis, hypothesis testing using F and t-tests, and evaluation of the coefficient of determination. According to the findings of this research, from 2021 through 2023, the Deferred Tax variable does not have a substantial impact on tax avoidance actions when the context is partial (t). In the context of tax evasion, the Debt Level variable is completely insignificant. From 2021 through 2023, companies that are included on the SRI-KEHATI Index do not let the factors dealing with their Deferred Tax and Debt Level have a major impact on the steps they take to avoid paying taxes (F). The level of debt and the amount of deferred taxes do not simultaneously affect tax evasion in SRI-KEHATI index companies listed on the Indonesia Stock Exchange.